Central debates in British politics - Fisher, Justin; Denver, D. T.; Benyon, John (Longman, 2003)
Debate ; Chronology ; Discussion Questions ; Part Three: Representation; 9 Political Parties: Organisational Change and Intra-Party Democracy ; Introduction ; Background ; Summary ; Theoretical Considerations; Summary ; Update ; Summary ; Debate; Summary ; Conclusion ; Chronology ; Discussion Questions ; 10 Elections and Voting ; Background; Theoretical Considerations ; Summary ; Electoral Systems ; Participation in Elections ; Summary ; Influences on Party Choice: A Dealigned Electorate; Conclusion ; Discussion Questions.